The impact of psychological empowerment on lecturer's innovative behavior in Malaysian private higher education institutions. - Abd. Ghani, Nik Azida; Raja Hussin, Tengku Ahmad Badrul Shah; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
Psychological empowerment comprising four cognitive dimensions i.e meaning, competence, autonomy and impact in the context of private higher education institutions was validated. The behavioral outcome of psychological empowerment was operationalized as innovative behavior. This study examined on a sample of 312 lecturers from 25 private higher education institutions in three states (Penang, Kedah and Kelantan) in Malaysia. The study verified the validity of the psychological empowerment scale of comprising four dimensions whereas innovative behaviour scale was unidimensional. Survey data was analyzed using correlation and regression analyses to assess the relationship between psychological empowerment and innovative behaviour as well as the impact of psychological empowerment on the behavioral outcome. The results indicate that psychological empowerment has significant relationship with innovative behaviour. Psychological empowerment is also found to be a significant predictor of innovative behavior (adjusted R2 = .109).